The Involvement of miRNA-375, miRNA-451, and IL-6 in the Immunopathogenesis of Hashimoto's Thyroiditis and Its Implications - Bashar A. Hadad; Wejdan Thamir Mahdi (OBAT: Jurnal Riset Ilmu Farmasi dan Kesehatan, 2025)
Hashimoto's thyroiditis (HT) is an autoimmune disorder that leads to thyroid dysfunction and chronic inflammation, often resulting in hypothyroidism. The exact mechanisms driving HT are not fully understood, but recent research has highlighted the potential role of various molecular markers in the disease’s pathogenesis. This study investigated the roles of miRNA-375, miRNA-451, and interleukin-6 (IL-6) in HT. Serum samples were collected from 100 HT patients and 100 healthy controls, and their expression levels were analyzed using quantitative polymerase chain reaction (qPCR) and enzyme-linked immunosorbent assay (ELISA). The results revealed significant alterations in the levels of these molecules. miRNA-375 was significantly elevated in HT patients (5.85 ± 1.30 vs. 1.0, p < 0.001), while miRNA-451 was markedly reduced (1.43 ± 0.22 vs. 10.91 ± 2.44, p < 0.001). Additionally, IL-6 levels were found to be significantly higher in HT patients (115.79 ± 12.62 vs. 21.34 ± 4.03 pg/ml, p < 0.001). These findings suggest that these molecules play critical roles in the immunopathogenesis of HT. Receiver operating characteristic (ROC) analysis further confirmed that miRNA-375, miRNA-451, and IL-6 are excellent diagnostic markers, with area under the curve (AUC) values ranging from 0.956 to 1.000. miRNA-375 showed 96% sensitivity and specificity at a cutoff >1.66-fold, while miRNA-451 demonstrated 100% sensitivity and specificity at a cutoff <3.48-fold. IL-6 also exhibited perfect diagnostic accuracy with 100% sensitivity and specificity at a cutoff >53.73 pg/ml. No significant variations were observed across demographic or treatment subgroups, supporting the stability of these biomarkers in clinical applications. These findings suggest that miRNA-375, miRNA-451, and IL-6 are dysregulated in HT and could serve as reliable biomarkers for diagnosis and potential therapeutic targets, offering new strategies for the management of Hashimoto’s thyroiditis.